The Effect Of Job Training And Work Motivation On Employee Performance At Pt Surya Nusantara Sentosa In The Jabodetabek And West Java Regions - Maharani, Aprilita Cintya; Stevianus , Stevianus (CV. Publikasi Indonesia, 2025)
This study aims to determine the influence of training and work motivation on the performance of employees of PT. Surya Nusantara Sentosan in the Jabodebatek and West Java regions. The analysis method in this study uses demographic descriptive analysis methods, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear analysis test, t test, f test and determination coefficient test. The data used in this study used case studies in journals and books that were continuous in this study and used questionnaire instruments, and valid data were collected by 100 respondents. This study uses the SPSS 29.0 testing tool. The results of this study show that the variables that the job training variable has a positive value and has a partial effect on employee performance, the work motivation variable has a positive value and has a partial effect on employee performance. Job training and work motivation have a positive value and have a simultaneous effect on employee performance. And the contribution of the variables of job training and work motivation simultaneously to employee performance is quite small, which is 23.7%.